Les jeudis d’Émile Zola - Alain Pagès (Flaubert: Revue Critique et Génétique)
We examine the regular Thursday night get-togethers Zola used to have during most of his life : the writer gathered at his home his closest friends, in particular his disciples of the naturalist school. We draw a picture of the guests who met there, and we try to reconstitute the atmosphere of these evenings, characterized by a great simplicity. A final section compares these Parisian Thursdays to the “Médan evenings” associated with the collection of short stories, “Les Soirées de Médan”, published in April 1880.